A Sand Fly Lutzomyia longipalpis (Lutz and Neiva) (Insecta: Diptera: Psychodidae: Phlebotominae) - Maria C. Carrasquilla; Phillip E. Kaufman (EDIS, 2015)
The true sand flies are densely covered with setae, have long slender legs, and broad and pointed wings that are held erect at rest. Several phlebotomine species are vectors of the protozoan parasites in the genus Leishmania, that are the causal agents of leishmaniasis. Visceral leishmaniais is the most severe form of the disease, and is fatal to the human or dog host if untreated. This 6-page fact sheet was written by Maria C. Carrasquilla and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, June 2015. (Photo credit: Cristina Ferro, Instituto Nacional de Salud, Colombia